S2 Doctor's perceptions of efficacy, safety and use of e-cigarettes in the united kingdom. (12th November 2019) - Gates, JC; Heiden, E; Amos, M; Brown, T; Rupani, H; Hicks, A; Chauhan, AJ
Abstract : Background: Since the introduction of electronic cigarettes (e-cigarettes) there has been a rapid rise in their popularity and use. Public Health England encourage their use as part of a smoking cessation strategy in contradiction with many worldwide institutions. On a day to day basis, front line healthcare professionals are being asked to advise their patients about e-cigarettes; therefore their beliefs and opinions are being relied upon. Aims: To explore the opinions and practices of UK doctors regarding e-cigarettes, including their safety, and examine for any difference in advice given to patients. Methods: A cross-sectional anonymous survey was developed by Respiratory Physicians in QAH, Portsmouth and distributed nationally to a sample of doctors from all specialities and grades over a 6 week period from April 2019. Results: A total of 571 participants responded and we analysed the data of 524. 47 were excluded either because of incomplete answers or if not from doctors working in the UK. Responders included qualified GPs (14%), consultants (30%), registrars, GP registrars or staff grade doctors (39%), core trainees (9%) and foundation trainees (8%). The largest speciality group of respondents were GPs (22%), followed by non-respiratory medical specialities (20%) and Respiratory specialists (19%). 12% had used an e-cigarette and 1.5% were current smokers. 60% wanted more training in this area. There was a wide spread in opinions regarding the perceived safety of e-cigarettes (figure 1) with an average 55.8±26 and range of 0–100. Personal smoking habits significantly influenced safety perceptions. A thematic analysis revealed four key themes: uncertainty due to a lack of evidence, pragmatism due to the known risks of traditional smoking, ambivalence due to a lack of awareness and a considerable concern negating their use. Conclusions: There is a wide variation in beliefs and practice of UK doctors, despite policies intended to encourage e-cigarette use. Patients are receiving conflicting advice regarding their use which is likely to continue until further educational resources are available, and doctors can be confident in the safety and long term evidence for e-cigarettes.